2013
DOI: 10.1177/216507991306101006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Cardiovascular Risk Reduction Program at a Workplace Medical Clinic

Abstract: The Cardiovascular Risk Reduction Program (CVRRP) was implemented in the 3M Medical Clinic in December 2009. The goal of the CVRRP was to evaluate 3M employees at risk for developing cardiovascular disease (CVD) and address any related modifiable risk factors with appropriate intervention strategies through clinic visits with a 3M nurse practitioner or physician and, if needed, a registered dietitian and/or exercise professional. Data for the first 100 participants were analyzed to initially assess the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Only 6 of the 22 included studies involved randomized, experimental designs to test the effects of a workplace intervention [30,35,[39][40][41]46]. The remaining 16 studies were designed as either quasi-experimental (n = 5) with no randomization to groups but with comparisons between a treatment and an existing control group [27,29,33,36,42], or as a one-group pre-test posttest study (n = 11) [28,31,32,34,37,38,[43][44][45]47,48]. One large study involved the testing of a digital health intervention that was incorporated as part of an employer insurance company across 42 states in the U.S. [47].…”
Section: Study Designs and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 6 of the 22 included studies involved randomized, experimental designs to test the effects of a workplace intervention [30,35,[39][40][41]46]. The remaining 16 studies were designed as either quasi-experimental (n = 5) with no randomization to groups but with comparisons between a treatment and an existing control group [27,29,33,36,42], or as a one-group pre-test posttest study (n = 11) [28,31,32,34,37,38,[43][44][45]47,48]. One large study involved the testing of a digital health intervention that was incorporated as part of an employer insurance company across 42 states in the U.S. [47].…”
Section: Study Designs and Methodsmentioning
confidence: 99%
“…Six of the 14 studies that measured blood pressure reported statistically significant improvements [33,40,[42][43][44]46]. And 6 of the 10 studies that measured A1C reported statistically significant reductions [28,29,31,40,41,43].…”
Section: Intervention Effects/outcomesmentioning
confidence: 97%
“…O trabalhador acima de 40 anos deve ser uma prioridade nas ações de intervenção que possam favorecer a prevenção da hipertensão e do diabetes, sendo necessária atenção especial à alimentação e à prática de exercícios, que favoreçam o controle da obesidade e a alteração do perfil lipídico 15 . De fato, existem estudos que comprovam a efetividade de programas educativos e de acompanhamento na redução de fatores de risco 20,21 , incluindo programas não-formais de exercícios doméstico e comunitários 22 . De acordo com o posicionamento oficial do igura 4: Percentual dos fatores de risco para doença coronariana de homens trabalhadores de uma siderúrgica (n = 776).…”
Section: Discussionunclassified
“…Já existem estudos que comprovam a efetividade de programas educativos e de acompanhamento na redução de fatores de risco para as doenças cardiovasculares (ANDRES et al, 2013). No entanto, o principal desafio envolvendo estudos sobre a relação entre determinantes sociais e saúde é estabelecer uma hierarquia de determinação dos fatores de risco mais amplos, como sociais, econômicos e políticos.…”
Section: Contextualização Das Doenças Cardiovascularesunclassified